TASK1 and TASK3 Are Coexpressed With ASIC1 in the Ventrolateral Medulla and Contribute to Central Chemoreception in Rats - Wang, Xia; Guan, Ruijuan; Zhao, Xiaomei; Zhu, Danian; Song, Nana; Shen, Linlin (Frontiers in Cellular Neuroscience, 2018)
The ventrolateral medulla (VLM), including the lateral paragigantocellular nucleus (LPGi) and rostral ventrolateral medulla (RVLM), is commonly considered to be a chemosensitive region. However, the specific mechanism of chemoreception in the VLM remains elusive. Acid-sensing ion channels (ASICs), a family of voltage-independent proton-gated cation channels, can be activated by an external pH decrease to cause Na+ entry and induce neuronal excitability. TWIK-related acid-sensitive potassium channels (TASKs) are members of another group of pH-sensitive channels; in contrast to AISICs, they can be stimulated by pH increases and are inhibited by pH decreases in the physiological range. Our previous study demonstrated that ASICs take part in chemoreception. The aims of this study are to explore whether TASKs participate in the acid sensitivity of neurons in the VLM, thereby cooperating with ASICs. Our research demonstrated that TASKs, including TASK1 and TASK3, are colocalized with ASIC1 in VLM neurons. Blocking TASKs by microinjection of the non-selective TASK antagonist bupivacaine (BUP), specific TASK1 antagonist anandamide (AEA) or specific TASK3 antagonist ruthenium red (RR) into the VLM increased the integrated phrenic nerve discharge (iPND), shortened the inspiratory time (Ti) and enhanced the respiratory drive (iPND/Ti). In addition, microinjection of artificial cerebrospinal fluid (ACSF) at a pH of 7.0 or 6.5 prolonged Ti, increased iPND and enhanced respiratory drive, which were inhibited by the ASIC antagonist amiloride (AMI). By contrast, microinjection of alkaline ACSF decreased iPND and respiratory drive, which were inhibited by AEA. Taken together, our data suggest that TASK1 and TASK3 are coexpressed with ASIC1 in the VLM. Moreover, TASK1 and TASK3contribute to the central regulation of breathing by coordinating with each other to perceive local pH changes; these results indicate a novel chemosensitive mechanism of the VLM.